A 40-year-old woman 'off legs'. (3rd January 2013) - Mehrotra, Prerna; Bhalla, Ashish
Abstract : We present the case of a 40-year-old woman with progressive lower-limb weakness resulting in an inability to mobilise independently. This was associated with a degree of confusion and shortness of breath on exertion. This case illustrates rare and severe complications of vitamin B12 deficiency, namely subacute combined degeneration of the spinal cord, megaloblastic anaemia and impaired cognitive function. The patient's condition improved considerably with adequate early resuscitation, followed by administration of synthetic vitamin B12 analogues and neuro-rehabilitation.